Tolerance induction to saline stress in papaya seeds treated with potassium nitrate and sildenafil citrate - Rafael Fonsêca Zanotti; José Carlos Lopes; Ludymila Brandão Motta; Allan Rocha de Freitas; Liana Hilda Golin Mengarda (Semina: Ciências Agrárias, 2013)
Papaya fruit (Carica papaya) is a species of great commercial agriculture importance. Although has a saline stress sensitivity. Potassium nitrate (KNO3) and nitric oxide are substances that inducing saline stress tolerance. The aim of this study was evaluate the effects of sildenafil citrate (SC) and KNO3 on the papaya seeds germination of under saline stress. Papaya seeds of hybrids Calimosa and JS12x Waimanalo were immersed in distilled water or KNO3 solutions and SC and followed germinated in distilled water or NaCl solution –0.3 MPa. Seeds of the hybrid JS12x Waimanalo had higher percentages of germination and normal seedlings. The controls of the two hybrids did not show saline stress tolerance during germination. Seeds of the hybrid JS12x Waimanalo, when treated with KNO3 or SC showed stress tolerance. The growth regulators tested were important in the induction of saline tolerance in papaya seeds.